Dead even - Meltzer, Brad. (New York : Rob Weisbach Books, 1998)
Young assistant district attorney Sara Tate finds herself going head to head with her defense attorney husband, Jared, in a case in which not only is the outcome at stake, but also both of their lives.
Keywords: Public prosecutors -- New York (State) -- New York -- Fiction; Burglary -- New York (State) -- New York -- Fiction; Intimidation -- New York (State) -- New York -- Fiction; New York (N.Y.) -- Fiction; Legal stories